A summarization of image and video databases for emotion recognition - Ashraf, Arselan; Gunawan, Teddy Surya; Abdul Rahman, Farah Diyana; Kartiwi, Mira (Springer, 2020)
In the past decades, human-computer interaction has become increasingly signifi-cant in our day to day lives. Many kinds of research have been conducted in the area of memory research, depression detection, and behavioural insufficiency identification, lie detection (covered up), and emotion recognition. Thus, the quantity of nonexclusive feeling and image/video databases or those custom-made to precise requirements have become enormous. In this way, an extensive yet minimal guide is expected to assist analysts with finding the most appropriate image/video database and comprehend what sorts of image/video databases as of now exist. In this paper, different elicitation strategies are discussed, and the da-tabases are basically categorized into a slick and enlightening comparison table in order to be used for emotion recognition model.